THINK-ALOUD METHOD: DEVELOPING STUDENTS' READING COMPREHENSION - Dita Ayu Pratiwi; Norani Norani (EEAL Journal (English Education and Applied Linguistics Journal), 2022)
The think-aloud method is a way for increasing reading comprehension. The think-aloud is a method that can help teachers in gathering student processes such as surmising and utilization of prior information. This research investigate the effectiveness of think aloud method in teaching students’ reading comprehension. Non-probability sampling was employed for choose learners from a state Junior High School in Garut for the quasi experimental research. The research sample consisted of class VIII for the experiment and control group. Through using pretest and posttest, the researcher gathered and statistically analyzed the data. The value of Sig evidences (2-tailed) is equal to 0.006 < 0.05, which means, the think-aloud method is not effective in teaching students' reading comprehension.